Octupole deformation in the nuclear chart based on the 3D Skyrme Hartree–Fock plus BCS model. (19th May 2017) - Ebata, Shuichiro; Nakatsukasa, Takashi
Abstract: We have performed a systematic study of the ground state for 1002 even–even nuclei in which 28 octupole-deformed nuclei are found. The interplay between the spatial deformation and the pairing correlation plays an important role in the nuclear structure. Our model is based on the Skyrme Hartree–Fock plus BCS model represented in the three-dimensional Cartesian coordinate space, which can describe any kind of nuclear shape. The quadrupole and octupole deformed nuclei appear in the mass region with characteristic neutron and proton numbers which are consistent with previous studies. In our results, there appear only pear shapes ( β 30 ) in the octupole deformed nuclei. We investigate the potential energy surfaces as functions of the octupole deformations ( β 3 m ; m = 0, 1, 2, 3), which tells us that 220 Rn also has local minima in the β 31 and β 32 potential energy surfaces.